The Role of Transfer prices in the Segmental reports as a tool for Measuring and Evaluating Performance: An applied study at Zebrano for Mobliat Furniture / Ltd. - Kosar Najmalddin Mohammed; Parzheen Shekh Mohammed Aziz (QALAAI ZANIST JOURNAL, 2020)
The companies that have branches needs to follow the activities of its various branches, and one of the activities that the administration follows is segmental reports, as an income statement is prepared for each branch of the unit and in a way that helps in assessing the performance of the work of each branch and provides information on the extent of their contributions in Achieving profits for the company, and for segmental reports to be prepared. The transfer pricing method must be followed to transfer products from one branch to another. The transfer price provides the branches a degree of autonomy for making their administrative decisions. An appropriate transfer price must be used to achieve the objectives’ balance of the transferor and the transferee branches, consequently the goals of the company as a whole are achieved. The problem with the study is that do the administrative cadres in the company aware of modern policies for pricing the products transferred between the branches of the company? And does the transfer prices contribute to evaluating the performance of the company branches through segmental reports? The study aims to know the transfer prices and their application as a tool to evaluate the performance of the branches in the companies that have branches. And knowing the extent of applying the transfer prices policy in the research sample company. As well as determining the role of its contribution in evaluating the performance of the branches of the research sample company through preparing segmental reports. The researchers concluded that the best way to price transfers that achieve the goal of the company as a whole, is the transfer price based on the market price. As for the purchasing branches (Erbil and Sulaymaniyah), the best way to price the transferred products is the variable cost method. Thus, the market price mayn’t be desirable for the managers of the purchasing branches, if their performance is evaluated. Conversely, the variable cost method may be desirable by managers because it increases the branches’ operating income. This leads to goals’ conflict between the company and its subsidiaries, as the company sells to its branches. Among the most important recommendations of the research is the necessity of preparing segmental reports in detail for each branch and following the use of transfer prices to transfer products between them, which show the performance of each of the company’s branches, follow-up and evaluating of the performance of branch managers in appropriate manner to the company’s goals.